Yolk-shell type carbon composite iron nitride negative electrode material as well as preparation method and application thereof

By preparing Yolk-shell carbon composite iron nitride negative electrode materials, the problem of unstable structural material of sodium ion battery negative electrode materials was solved, higher cycle stability and conductivity were achieved, cost was reduced, and battery performance was improved.

CN120749138APending Publication Date: 2025-10-03SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510863309.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode materials have poor battery cycle performance due to structural instability.

Method used

A Yolk-shell carbon composite iron nitride negative electrode material is used, including an outer shell and an inner core structure. The outer shell is a carbon shell and the inner core is a cubic iron nitride. A composite material with a hollow structure is formed through a preparation method, which improves the specific surface area and conductivity of the material and buffers volume changes.

Benefits of technology

It significantly improves the cycle stability and conductivity of sodium-ion batteries, reduces costs, and increases the overall energy density and cycle life of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120749138A_ABST
    Figure CN120749138A_ABST
Patent Text Reader

Abstract

The invention provides a Yolk-shell type carbon composite iron nitride negative electrode material as well as a preparation method and application thereof. The Yolk-shell type carbon composite iron nitride negative electrode material comprises a shell, a cavity surrounded by the shell and an inner core arranged in the cavity, and the particle size of the Yolk-shell type carbon composite iron nitride negative electrode material is 180-400 nm; the shell is a carbon shell, and the thickness of the carbon shell is 10nm-30nm; the inner core is cubic iron nitride, and the particle size of the cubic iron nitride is 60-180 nm. The Yolk-shell type carbon composite iron nitride negative electrode material provided by the invention has a larger specific surface area, so that the contact between an electrolyte and an electrode is improved, the diffusion path of Na < + > transmission is reduced, and finally, the obtained sodium ion battery shows higher cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a Yolk-shell carbon composite iron nitride negative electrode material, a preparation method thereof, and applications thereof. Background Art

[0002] Sodium-ion batteries (SIBs), as an emerging secondary battery technology, have attracted widespread attention in recent years due to their potential applications in large-scale energy storage systems. Compared with lithium-ion batteries, SIBs have the advantages of low cost, abundant resources and environmental friendliness. Especially considering the uneven distribution of global lithium resources and the high mining costs, sodium-ion batteries are seen as a more sustainable solution for future energy storage systems. The working principle of sodium-ion batteries is similar to that of lithium-ion batteries, which store and release charges by embedding and de-embedding sodium ions in positive and negative electrode materials. However, the larger size of sodium ions The high charge density makes the embedding and de-embedding process in battery materials more complicated, and puts higher requirements on the structural stability and electrochemical performance of the materials.

[0003] Currently, a great deal of effort has been invested in designing anode materials suitable for SIBs, such as carbon materials, alloy materials, and conversion materials. Although some progress has been made in the research of anode materials for SIBs, existing materials still fail to fully meet the needs of practical applications. For example, although carbon-based materials have high stability and good cycling performance, their low sodium storage capacity limits the improvement of the overall energy density of the battery. Although alloy materials have high sodium storage capacity, their large volume changes during charge and discharge often lead to damage to the material structure, affecting the cycle life of the battery. Transition metal oxides have poor conductivity and require additional conductive additives, which increases the complexity and cost of battery manufacturing. Transition metal nitrides, such as Fe3N, although they have high theoretical capacity and good electronic conductivity, have not yet been fully addressed. The problems of volume change and structural stability during the sodium ion insertion / deinsertion process have not been fully solved, especially in terms of cycling stability and rate performance at high current density.

[0004] For the negative electrode materials of SIBs, especially the transition metal nitrides (TMNs) of group IVB-VIB, they have superior properties such as higher electronic conductivity and relatively low conversion reaction potential, and have become one of the most promising negative electrode materials for metal ion batteries (MIBs), and are expected to obtain excellent kinetic performance during the electrochemical reaction. TMNs include TiN, Fe3N, Fe2N, VN, Mo2N, FeN, Ni3N, CrN, NbN and MoN. Among them, iron nitride (Fe xN, x = 2, 3) has attracted widespread attention due to its high theoretical value, high ionic conductivity, high electronic conductivity, good environmental friendliness, and low cost. In addition, iron nitride as the anode of SIBs exhibits ultrafast charge transfer pseudocapacitive behavior due to its stable phase transition, and the discharge product Na3N also has good ionic conductivity. These advantages make iron nitride an ideal candidate anode material for SIBs. However, similar to other conversion-type anode materials, iron nitride also undergoes huge volume changes during the sodium insertion / deintercalation process, which can cause the active material to agglomerate or the active material to be violently crushed and fall off from the current collector, resulting in rapid capacity decay of the iron nitride electrode.

[0005] In response to these challenges, researchers have proposed a series of strategies to improve the performance of SIBs negative electrode materials. Among them, constructing materials with unique microstructures has become a research hotspot. By designing the microstructure of the material, such as porous, hollow or yolk-shell structure, the stress caused by volume change can be effectively alleviated, and the structural stability and cycle life of the material can be improved. However, the preparation of special microstructure materials places higher demands on the synthesis process. How to accurately control the microscopic characteristics and chemical composition of the obtained materials has become the key to achieving high-performance SIBs negative electrode materials.

[0006] Based on this, how to provide a sodium ion battery negative electrode material with fine and stable structure and superior performance so that the sodium ion battery in which it is located exhibits better cycle stability is one of the important technical problems that need to be solved in this field. Summary of the Invention

[0007] The main purpose of the present invention is to provide a Yolk-shell type carbon composite iron nitride negative electrode material, its preparation method and application, so as to solve the problem of poor battery cyclability caused by the structural instability of the negative electrode active material of sodium ion batteries in the prior art.

[0008] To achieve the above-mentioned objectives, a first aspect of the present invention provides a Yolk-shell type carbon composite iron nitride negative electrode material, comprising an outer shell, a cavity formed by the outer shell, and an inner core arranged in the cavity, wherein the particle size of the Yolk-shell type carbon composite iron nitride negative electrode material is 180nm to 400nm; the outer shell is a carbon shell, and the thickness of the carbon shell is 10nm to 30nm; the inner core is a cubic iron nitride, and the particle size of the cubic iron nitride is 60nm to 180nm.

[0009] Furthermore, in the cubic iron nitride, the molar ratio of iron element to nitrogen element is (2-4):1.

[0010] Furthermore, based on the total weight of the Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 60% to 85%, preferably 60% to 80%.

[0011] Furthermore, the particle size of the Yolk-shell carbon composite iron nitride negative electrode material is 200nm to 260nm; the thickness of the carbon shell is 20±2nm; and the particle size of the cubic iron nitride is 90nm to 125nm.

[0012] A second aspect of the present invention provides a method for preparing the above-mentioned Yolk-shell carbon composite iron nitride negative electrode material, comprising: step S1, preparing a cubic iron oxide precursor; step S2, adding the cubic iron oxide precursor, a polymer monomer and an alkaline pH regulator to a solvent to prepare a mixed slurry; stirring the mixed slurry so that the polymer monomer polymerizes on the surface of the cubic iron oxide precursor to form a polymer layer, thereby obtaining a first product; step S3, calcining the first product to convert the polymer layer into a carbon shell, thereby obtaining a second product; step S4, etching the cubic iron oxide precursor in the second product to reduce the cubic volume of the cubic iron oxide precursor and form a cavity, thereby obtaining a third product; step S5, nitriding the third product to convert the reduced cubic iron oxide precursor into cubic iron nitride, thereby obtaining a Yolk-shell carbon composite iron nitride negative electrode material.

[0013] Furthermore, step S1 also includes: step S1-1, adding an iron source and an oxygen source to water to obtain a mixed solution; step S1-2, the mixed solution is sequentially subjected to a first reaction and a second reaction to obtain a cubic iron oxide precursor; the molar ratio of the iron element in the iron source to the oxygen element in the oxygen source is 1: (2.7~3.0); and / or the reaction temperature of the first reaction is 60℃~80℃, and the reaction time is 20min~40min; and / or the reaction temperature of the second reaction is 80℃~120℃, the reaction time is 4 days~6 days, and the second reaction is carried out in a reactor; preferably, the iron source is selected from one or more of ferric chloride, ferric sulfate and ferric nitrate; and / or, the oxygen source is selected from one or more of hydroxides; more preferably, the hydroxide is added in the form of an aqueous solution with a molar concentration of 5M~6M, and the hydroxide is sodium hydroxide and / or potassium hydroxide.

[0014] Furthermore, in step S2, the weight ratio of the cubic iron oxide precursor to the polymer monomer is 1:(3.5~7.5), preferably 1:(4.4~4.5); and / or the volume ratio of the solvent to the alkaline pH regulator is (200±20):1; and / or the stirring time is 6h~10h; and / or, preferably, the alkaline pH regulator is NH4OH; more preferably, the polymer monomer includes resorcinol and formaldehyde, and the polymer layer is a resorcinol-formaldehyde layer; or, the polymer monomer is dopamine, and the polymer layer is a polydopamine layer.

[0015] Furthermore, in step S3, the heating rate of the calcination treatment is 2°C / min to 3°C / min, the holding temperature is 500°C to 600°C, and the holding time is 2h to 6h; preferably, the calcination treatment is carried out under a protective atmosphere, and the protective atmosphere is nitrogen and / or argon.

[0016] Furthermore, in step S4, the etching treatment includes: immersing the second product in an acidic etching solution with a concentration of 3M to 5M, and stirring for 1h to 3h to obtain a third product; preferably, the acidic etching solution is selected from one or more of hydrochloric acid aqueous solution, nitric acid aqueous solution, phosphoric acid aqueous solution and hydrofluoric acid aqueous solution.

[0017] Furthermore, in step S5, the nitriding treatment includes the following steps: a heating stage in a protective atmosphere, a heat preservation stage in a nitrogen source atmosphere, and a cooling stage in a protective atmosphere; preferably, the heating rate in the heating stage is 2°C / min to 3°C / min, until the temperature reaches 500°C to 700°C; the heat preservation temperature in the heat preservation stage is 550°C to 700°C, and the heat preservation time is 3h to 5h; more preferably, the nitrogen source atmosphere is an ammonia atmosphere; and / or, the protective atmosphere is nitrogen and / or argon; further preferably, the ammonia atmosphere is realized by: introducing ammonia into the nitriding system; and / or, adding ammonia water to the nitriding system.

[0018] A third aspect of the present invention provides a negative electrode plate, which includes the above-mentioned Yolk-shell type carbon composite iron nitride negative electrode material; or, the negative electrode plate includes the Yolk-shell type carbon composite iron nitride negative electrode material prepared by the preparation method of the above-mentioned Yolk-shell type carbon composite iron nitride negative electrode material.

[0019] A fourth aspect of the present invention provides a sodium ion battery, comprising a negative electrode plate, which is the above-mentioned negative electrode plate.

[0020] The technical solution of the present invention provides a Yolk-shell carbon composite iron nitride negative electrode material, which has a larger specific surface area, thereby helping to improve the contact between the electrolyte and the electrode and reduce Na+ At the same time, compared with solid structures with similar components, the special Yolk-shell structure can effectively shorten the charge transfer path, suppress the stress caused by volume change, avoid the expansion and agglomeration of nitrides, improve reaction stability and conductivity, and ultimately make the resulting sodium-ion battery exhibit higher cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings, which constitute part of this application, are intended to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are intended to explain the present invention and do not constitute an undue limitation of the present invention. In the accompanying drawings:

[0022] Figure 1 Schematic diagram of the preparation reaction route of the Yolk-shell carbon composite iron nitride negative electrode material in Example 1 of the present invention;

[0023] Figure 2 This is a scanning electron microscope image of the cubic iron oxide, i.e., Fe2O3 cube, obtained in Example 1 of the present invention;

[0024] Figure 3 This is a scanning electron microscope image of the first product obtained in Example 1 of the present invention, namely Fe2O3@RF;

[0025] Figure 4 This is a scanning electron microscope image of the second product obtained in Example 1 of the present invention, namely Fe3O4@C;

[0026] Figure 5 This is a transmission electron microscope image of the second product obtained in Example 1 of the present invention, namely Fe3O4@C;

[0027] Figure 6 This is a scanning electron microscope image of the third product obtained in Example 1 of the present invention, namely Yolk-shell Fe3O4@C;

[0028] Figure 7 This is a scanning electron microscope image of the Yolk-shell carbon composite iron nitride negative electrode material obtained in Example 1 of the present invention;

[0029] Figure 8 This is a transmission electron microscope image of the Yolk-shell carbon composite iron nitride negative electrode material obtained in Example 1 of the present invention;

[0030] Figure 9 This is the X-ray diffraction pattern of the Yolk-shell carbon composite iron nitride negative electrode material obtained in Example 1 of the present invention;

[0031] Figure 10This is a Raman spectrum of the Yolk-shell carbon composite iron nitride negative electrode material obtained in Example 1 of the present invention;

[0032] Figure 11 This is an SEM image of the composite negative electrode material obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0033] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the embodiments.

[0034] As described in the background art, the negative electrode active materials of sodium ion batteries in the prior art have the problem of poor battery cyclability due to structural instability. In order to solve the above technical problems, the first aspect of the present invention provides a Yolk-shell type carbon composite iron nitride negative electrode material, comprising an outer shell, a cavity formed by the outer shell, and an inner core disposed in the cavity, wherein the particle size of the Yolk-shell type carbon composite iron nitride negative electrode material is 180nm to 400nm; the outer shell is a carbon shell with a thickness of 10nm to 30nm; the inner core is a cubic iron nitride with a particle size of 60nm to 180nm.

[0035] The Yolk-shell carbon composite iron nitride negative electrode material provided by the present invention has a larger specific surface area, which helps to improve the contact between the electrolyte and the electrode and reduce Na + At the same time, compared with solid structures with similar components, the special Yolk-shell structure can effectively shorten the charge transfer path, suppress the stress caused by volume change, avoid the expansion and agglomeration of nitrides, improve reaction stability and conductivity, and ultimately make the resulting sodium-ion battery exhibit higher cycle stability.

[0036] Specifically, the particle size range of the Yolk-shell carbon composite iron nitride negative electrode material (hereinafter referred to as the composite negative electrode material) is limited to 180nm~400nm, which is between the nanoscale and micron scale. It can not only ensure the high specific surface area of ​​the composite negative electrode material to enhance the interfacial reaction activity, but also prevent the composite negative electrode material from excessively agglomerating during the electrochemical process, maintaining good dispersibility and electrochemical activity. In addition, the carbon shell is used as the outer shell, and its thickness is controlled between 10nm~30nm, which can effectively protect the core active metal compound from electrolyte corrosion, while providing a good electron conduction path, significantly improving the conductivity of the composite negative electrode material. At the same time, the carbon shell can also buffer the volume change of the internal active material during the charge and discharge process, avoid cracking, and increase the stability and cycle life of the structure. The inner core is set to a cubic iron nitride with a particle size of 60nm~180nm, thereby providing a higher theoretical capacity and good ion diffusion characteristics, thereby providing sufficient electrochemical active sites. Compared with traditional solid structures with similar chemical compositions, the uniqueness of the Yolk-shell structure lies in the existence of internal cavity voids. This void allows the volume of the internal active material to change during charge and discharge without destroying the carbon shell, ensuring the long-term stability and excellent electrochemical performance of the composite negative electrode material.

[0037] Furthermore, in the structure of the Yolk-shell type carbon composite iron nitride negative electrode material, there is a hollow structure between the outer carbon shell and the inner core of the cavity, and the size of the hollow structure is 40nm to 55nm.

[0038] On the basis of the above, in order to better control the electrochemical performance of the resulting composite negative electrode material, the molar ratio of iron to nitrogen in the cubic iron nitride is preferably (2-4):1. This molar ratio can make the composition of the cubic iron nitride material as the core close to that of an ideal iron nitride, such as FeN or Fe3N, thereby more effectively improving the stability and high sodium storage performance of the resulting composite negative electrode material. In several preferred embodiments, the cubic iron nitride is cubic Fe3N because Fe3N has a higher theoretical specific capacity and its cubic structure is conducive to increasing the stacking density of the material, showing higher reversibility in the electrochemical process, and thus can more significantly improve the cycle stability of the battery.

[0039] Furthermore, based on the total weight of the Yolk-shell carbon composite iron nitride negative electrode material as 100%, the weight proportion of the cubic iron nitride is 60% to 85%, preferably 60% to 80%, so as to facilitate the composite negative electrode material to have both sufficient active ingredients (iron nitride) to provide high specific capacity and sufficient carbon material to ensure electron transport and structural stability, thereby more effectively improving the various performances of the final sodium ion battery.

[0040] In several preferred embodiments, a carbon shell that is too thin may not adequately protect the core and provide good conductivity, while an excessively thick carbon shell may lead to isolation of active sites. Therefore, to more precisely control and enhance the conductivity and structural stability of the composite negative electrode material, a carbon shell thickness of 20±2 nm is preferred. Furthermore, to better coordinate the structure of each layer, the particle size of the Yolk-shell carbon composite iron nitride negative electrode material is further preferably 200nm to 260nm, and the particle size of the cubic iron nitride is 90nm to 125nm, thereby obtaining a Yolk-shell carbon composite iron nitride negative electrode material with a more stable structure and superior electrochemical performance.

[0041] In several more preferred embodiments, the Raman spectrum of the Yolk-shell carbon composite iron nitride negative electrode material includes D and G peaks, and the intensity ratio of the D peak to the G peak, ID / IG, is 0.85 to 0.95. In the Raman spectrum test results, ID / IG reflects the degree of graphitization of the carbon material. In addition to having the above-mentioned special microstructure, the composite negative electrode material provided by the present invention also has the above-mentioned graphitization characteristics in its carbon shell, which not only improves the conductivity of the composite negative electrode material, but also indirectly promotes close contact between the core iron nitride and the carbon shell, enhancing the integrity and cycle stability of the entire composite material.

[0042] A second aspect of the present invention provides a method for preparing the above-mentioned Yolk-shell carbon composite iron nitride negative electrode material, comprising: step S1, preparing a cubic iron oxide precursor; step S2, adding the cubic iron oxide precursor, a polymer monomer and an alkaline pH regulator to a solvent to prepare a mixed slurry; stirring the mixed slurry so that the polymer monomer polymerizes on the surface of the cubic iron oxide precursor to form a polymer layer, thereby obtaining a first product; step S3, calcining the first product to convert the polymer layer into a carbon shell, thereby obtaining a second product; step S4, etching the cubic iron oxide precursor in the second product to reduce the cubic volume of the cubic iron oxide precursor and form a cavity, thereby obtaining a third product; step S5, nitriding the third product to convert the reduced cubic iron oxide precursor into cubic iron nitride, thereby obtaining a Yolk-shell carbon composite iron nitride negative electrode material.

[0043] For the above Yolk-shell carbon composite iron nitride negative electrode material, the present invention provides a preparation process from the initial preparation of iron oxide cubes to the final composite material molding, involving microstructural changes and performance improvements, thereby obtaining a composite negative electrode material with superior performance, especially strong stability. Figure 1As shown, iron oxide cubes were first synthesized as a starting template. Next, polymer-coated core-shell spheres were prepared through co-assembly polymerization of polymer monomers. During this process, the resulting resin was uniformly deposited on the surface of the iron oxide nanocubic particles. The core-shell spheres were then subjected to calcination, etching, and nitridation to obtain a unique Yolk-shell carbon-composite iron nitride anode material.

[0044] Specifically: In step S1, the initial iron oxide cubes are formed, which helps to improve the overall structural stability of the material and provides a stable substrate for subsequent carbon coating and cavity creation. In steps S2 and S3, the polymerization of polymer monomers on the surface of the iron oxide forms a polymer layer, which is converted into a carbon shell during subsequent heat treatment, thereby achieving carbon coating. The formation of the carbon shell also stabilizes the microstructure of the material and prevents disintegration during subsequent treatment. In step S4, an etching treatment is performed to remove part of the iron oxide to form an internal cavity void, which is the core of the "yolk shell" structure. This structure can significantly alleviate the volume expansion pressure during the sodium ion insertion / deinsertion process, protect the outer carbon shell from damage, and ensure the cycle stability and rate performance of the resulting composite negative electrode material. The nitridation treatment in step S5 converts the iron oxide into iron nitride. This is because iron nitride has higher electronic conductivity and sodium storage performance than iron oxide. This transformation improves the electrochemical activity of the material and also increases the overall stability of the resulting composite negative electrode material.

[0045] Furthermore, step S1 further includes: step S1-1, adding an iron source and an oxygen source to water to obtain a mixed solution; and step S1-2, sequentially subjecting the mixed solution to a first reaction and a second reaction to obtain a cubic iron oxide precursor. Specifically, preferably, the sol-gel reaction and hydrothermal process are used to prepare Fe2O3 nanocubes with more controllable size, thereby providing a more stable core material template framework for subsequent structural modification.

[0046] In the above-mentioned preparation process of the cubic iron oxide precursor, in order to form iron oxide with higher purity and better crystallinity, the molar ratio of iron in the iron source to oxygen in the oxygen source is preferably 1: (2.7-3.0). In addition, in order to obtain nano-iron oxide cubes with more uniform size and clearer morphology, thereby more effectively improving the stability of the final iron nitride core, the reaction temperature of the first reaction is preferably 60°C to 80°C and the reaction time is 20min to 40min; and / or the reaction temperature of the second reaction is 80°C to 120°C and the reaction time is 4 days to 6 days, and the second reaction is carried out in a reactor. In several typical embodiments, the iron source is preferably selected from one or more of ferric chloride, ferric sulfate and ferric nitrate; and / or the oxygen source is selected from one or more hydroxides. In addition, for the above-mentioned oxygen source, it is preferably added in the form of an aqueous solution with a molar concentration of 5M to 6M during the preparation process, and the hydroxide is sodium hydroxide and / or potassium hydroxide. This preferred addition method, solution concentration, and oxygen source type help to further optimize the pH value of the reaction, promote the uniform growth of iron oxides, and make the structure of the final composite negative electrode material more stable.

[0047] Furthermore, during the actual preparation process, the preparation method provided by the present invention also involves multiple washing and drying processes. The washing process is performed using conventional procedures performed by those skilled in the art, such as using ethanol as a solvent and washing 3 to 5 times. Drying is also performed using conventional procedures performed by those skilled in the art, such as setting the drying temperature to 50°C to 70°C and the drying time to 10 to 15 hours.

[0048] In step S2, in order to more effectively optimize the thickness and density of the carbon shell, so that the subsequently formed carbon shell is not so thick as to affect the internal Na + The diffusion of the cubic iron oxide precursor is not too thin to effectively buffer the volume change. Specifically, the weight ratio of the cubic iron oxide precursor to the polymer monomer is preferably 1: (3.5-7.5), and more preferably 1: (4.4-4.5).

[0049] Furthermore, the stirring time is 6 to 10 hours, thereby more effectively controlling the deposition polymerization rate of the polymer monomers and the morphology of the formed polymer layer, thereby promoting the formation of a more stable carbon layer after subsequent calcination. Furthermore, the volume ratio of the solvent to the alkaline pH adjuster is preferably (200±20):1; and / or the alkaline pH adjuster is NH4OH, which can provide a milder and more suitable alkaline environment for the reaction medium, further promoting the uniform deposition of the polymer layer on the surface of the iron oxide cubes.

[0050] Regarding the type of polymer monomers and the polymer formed, in several typical embodiments, the polymer monomers include resorcinol and formaldehyde, and the polymer layer is a resorcinol-formaldehyde layer; or, the polymer monomer is dopamine, and the polymer layer is a polydopamine layer. Resorcinol (R) and formaldehyde (F) can co-assemble to form a resorcinol-formaldehyde (RF) resin, which grows uniformly and spontaneously and deposits on the surface of the iron oxide cubic nanoparticles, facilitating subsequent calcination to form a stable and continuous carbon layer. Dopamine can self-polymerize to form polydopamine, forming a continuous polymer layer under simpler reaction conditions and systems.

[0051] In several more typical embodiments, when the polymer monomers include resorcinol and formaldehyde, a surfactant, CTAB, is preferably added to the mixed slurry, and the weight ratio of the surfactant CTAB to the cubic iron oxide precursor is (15-16):1. This is because CTAB, a cationic surfactant, can not only promote the low-concentration polymerization of resorcinol and formaldehyde, but also promote the spontaneous growth of RF resin on the surface of the iron oxide nanocubes. Adding it to the reaction system at the above weight ratio can make the RF layer more uniformly distributed and of a more moderate thickness, while also suppressing the reduction of internal active sites caused by over-coating, thereby significantly optimizing the sodium storage capacity and electrochemical cycling performance of the resulting composite negative electrode material.

[0052] In step S3, the polymer layer is calcined to form a carbon layer. During this process, the calcination process preferably has a heating rate of 2°C / min to 3°C / min, a holding temperature of 500°C to 600°C, and a holding time of 2h to 6h. A heating rate of 2°C / min to 3°C / min helps to heat the first product more evenly, reducing cracking or structural inhomogeneity caused by excessive temperature gradients. A holding temperature of 500°C to 600°C effectively promotes carbon formation and simultaneously promotes the conversion of iron in the inner core iron oxide to a lower valence state, facilitating subsequent conversion to a structurally stable nitride. A holding time of 2h to 6h more effectively balances the integrity of the resulting carbon layer and the suppression of side reactions, ultimately resulting in a more stable carbon shell structure. Furthermore, in order to more effectively reduce the reaction of the intermediate product with other impurities in the air under high temperature conditions, thereby improving the purity and structural stability of the resulting composite negative electrode material, the calcination process is preferably carried out under a protective atmosphere, and the protective atmosphere is nitrogen and / or argon.

[0053] Furthermore, in step S4, the etching treatment includes: immersing the second product in an acidic etching solution with a concentration of 3M to 5M, and after stirring for 1h to 3h, obtaining a third product. Based on the structure and composition of the second product, the inventors further optimized the etching conditions through a large number of experiments, thereby more efficiently removing iron oxides with a more suitable thickness ratio, leaving behind the carbon shell and the iron oxide "yolk" of the core, creating a more stable internal loose space, thereby more significantly improving the material's cycle stability and rate performance. In addition, the acidic etching solution is preferably selected from one or more of hydrochloric acid aqueous solution, nitric acid aqueous solution, phosphoric acid aqueous solution and hydrofluoric acid aqueous solution.

[0054] In step S5, the inner core iron oxide is converted into iron nitride by nitriding treatment. In this process, it is preferred that the following steps are carried out in sequence: a heating stage in a protective atmosphere, a heat preservation stage in a nitrogen source atmosphere, and a cooling stage in a protective atmosphere. By setting up three calcination stages under different gas atmospheres, the interference of oxygen in the air on the material can be more effectively reduced, while promoting a smoother nitriding process, promoting the effective combination of iron and nitrogen elements, and making the conversion from iron oxide to high-purity iron nitride more complete, and ultimately significantly improving the chemical stability of the obtained composite negative electrode material. Based on the above-mentioned nitriding stage setting, it is further preferred that the heating rate of the heating stage is 2°C / min to 3°C / min until the temperature reaches 500°C to 700°C; the heat preservation temperature of the heat preservation stage is 550°C to 700°C, and the heat preservation time is 3h to 5h. Calcination under such more preferred conditions can make the crystals of the inner core iron nitride more ordered, while also more effectively maintaining the structure of the outer carbon shell, thereby making the structure of the resulting composite negative electrode material more complete and stable, and the electrochemical performance, especially the cyclability, better.

[0055] Furthermore, the nitrogen source atmosphere is preferably ammonia, a nitrogen-rich gas that provides sufficient nitrogen while promoting a more uniform conversion of iron oxide to iron nitride, resulting in a more stable core structure for subsequent applications. The protective atmosphere is preferably nitrogen and / or argon.

[0056] In actual application, the ammonia atmosphere is achieved by: introducing ammonia gas into the nitriding system; and / or, adding ammonia water into the nitriding system.

[0057] A third aspect of the present invention provides a negative electrode sheet comprising the aforementioned Yolk-shell carbon-composite iron nitride negative electrode material; or comprising a Yolk-shell carbon-composite iron nitride negative electrode material prepared by the aforementioned method for preparing a Yolk-shell carbon-composite iron nitride negative electrode material. Because the composite negative electrode material possesses a yolk-shell structure and a highly conductive carbon shell, while retaining the high sodium storage properties of iron nitride, its use in the negative electrode sheet can significantly improve the overall energy density and cycling stability of the sodium-ion battery in which it is used.

[0058] A fourth aspect of the present invention provides a sodium-ion battery comprising a negative electrode plate, the negative electrode plate being the above-described negative electrode plate. The above-described negative electrode plate, containing a unique and high-performance Yolk-shell carbon-composite iron nitride negative electrode material, exhibits superior electrical performance and stability, enabling the battery to demonstrate excellent cycle stability and rate performance during charge and discharge. This simultaneously reduces costs and improves safety, opening up new possibilities for the commercial application of sodium-ion batteries.

[0059] The present application is further described in detail below with reference to specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in this application.

[0060] Unless otherwise defined, all technical terms used hereinafter have the same meanings as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0061] Example 1

[0062] Preparation of a Yolk-shell carbon composite iron nitride negative electrode material, the reaction route diagram is shown in Figure 1 :

[0063] (1) Preparation of a cubic iron oxide precursor: 16.2 g of FeCl3, 50 mL of deionized water, and 50 mL of a 5.4 M sodium hydroxide solution (i.e., the molar ratio of the iron element in FeCl3 to the oxygen element in the sodium hydroxide is 1:2.7) were mixed to obtain a mixed solution, and the mixture was reacted in a water bath at 75°C for 30 min, i.e., the first reaction. The mixture was then transferred to a hydrothermal reactor and hydrothermally reacted at 100°C for 5 days, i.e., the second reaction. The mixture was then centrifuged, washed three times with water, three times with ethanol, and dried at 60°C to obtain the cubic iron oxide, which was designated as Fe2O3 cubes.

[0064] The scanning electron microscope (SEM) image of the obtained cubic iron oxide, i.e., Fe2O3 cube, is shown in FIG. Figure 2 .Depend on Figure 2It can be seen that the average particle size of the obtained Fe2O3 cubes is distributed in the range of 180nm to 240nm, and the uniformity is relatively good.

[0065] (2) Take 300mg Fe2O3 cubes, 280mL deionized water and 120mL ethanol, ultrasonicate for 30min, then add 4.6g CTAB, 0.7g resorcinol, 2mL NH4OH and 1.2mL formaldehyde in sequence to obtain a mixed slurry and stir for 8h. Resorcinol and formaldehyde are used as polymer monomers, and the weight ratio of Fe2O3 cubes to the total weight of these polymer monomers is 1:4.408; the weight ratio of surfactant CTAB to cubic iron oxide precursor is 15.3:1; NH4OH is used as an alkaline pH regulator, and the volume ratio of alcohol-water mixed solvent to the alkaline pH regulator is 200:1. During the stirring process, resorcinol (R) and formaldehyde (F) polymerize under the condition of CTAB as a surfactant to form resorcinol-formic acid (RF) resin and wrap the outer surface of Fe2O3. The obtained mixed slurry reaction liquid was centrifuged, washed with water 5 times, and dried at 60°C to obtain the first product, which was recorded as Fe2O3@RF;

[0066] The SEM image of the first product, Fe2O3@RF, is shown in Figure 3 As can be seen from the figure, after RF coating, under the premise of Fe2O3 as a template, a composite structure Fe2O3@RF uniformly attached to the surface of Fe2O3 cubes was synthesized.

[0067] (3) 2.4 g of the first product was taken and heated to 550 °C at a rate of 2 °C / min under an Ar atmosphere and kept at this temperature for 4 h. The mixture was then naturally cooled to room temperature to obtain the second product, which was recorded as Fe3O4@C.

[0068] The SEM image of the second product, Fe3O4@C, is shown in Figure 4 , transmission electron microscopy (TEM) images are shown in Figure 5 .Depend on Figure 4 and Figure 5 Compared to the Fe2O3 cubes, the second product, Fe3O4@C, exhibits a uniform carbon shell and a slightly rough and transparent surface, confirming successful uniform carbon coating. The carbon layer thickness is ~20 nm, indicating that the Fe3O4 in the composite is encapsulated in a carbon nanolayer structure.

[0069] (4) 1.4 g of the second product was added to 500 mL of 4 M hydrochloric acid as an etching solution and stirred for 1 h. During this process, a portion of the cubic iron oxide precursor was etched, forming a cavity structure. The mixture was centrifuged, washed three times with water, and dried at 60°C to obtain the third product, designated Yolk-shell Fe3O4@C.

[0070] The SEM image of the third product, Yolk-shell Fe3O4@C, is shown in Figure 6 .like Figure 6 As shown in the figure, after etching, the third product has a concave morphology, proving that the Yolk-shell Fe3O4@C composite structure was successfully prepared. In addition, the figure shows that the average particle size of the obtained third product is distributed between 200nm and 260nm.

[0071] (5) Take 30 mg of the third product, heat it to 600 °C at a rate of 2 °C / min under N2 atmosphere, which is the heating stage, then keep it at 600 °C for 3 h under NH3 atmosphere, which is the holding stage, and then naturally cool it to room temperature under N2 atmosphere to obtain a Yolk-shell type carbon composite iron nitride negative electrode material, which is recorded as Yolk-shell Fe3N@C.

[0072] The SEM image of the obtained Yolk-shell carbon composite iron nitride negative electrode material, namely Yolk-shell Fe3N@C, is shown in Figure 7 , TEM images show Figure 8 .like Figure 7 and Figure 8 As shown in the product obtained by nitridation of the Yolk-shell Fe3O4@C precursor with a nitrogen source, it can be seen that the Fe3N nanoparticles are well confined and distributed in interconnected carbon nanoshells with a hollow structure (thickness is about 20 nm).

[0073] The X-ray diffraction (XRD) pattern of the obtained Yolk-shell carbon composite iron nitride negative electrode material is shown in Figure 9 The horizontal axis of the spectrum is 2θ (°), and the vertical axis is intensity (au). Comparison with the standard diffraction pattern shows that the main diffraction peaks in the obtained composite anode material match the standard diffraction pattern of Fe3N (JCPDS: 73-2101), indicating that the iron nitride in the composite material belongs to a single Fe3N.

[0074] The Raman spectrum of the obtained Yolk-shell carbon composite iron nitride negative electrode material is shown in Figure 10 The horizontal axis in the spectrum is the Raman frequency shift (cm -1 ), the vertical axis is intensity (au). Figure 10 As shown, the Raman spectrum shows D peak and G peak, and the intensity ratio of D peak to G peak is I D / I G is 0.88, indicating that the obtained carbon shell is partially graphitic, which helps to improve the overall electronic conductivity of the obtained material.

[0075] The microstructure of the resulting Yolk-shell carbon-composite iron nitride anode material consists of a carbon shell, a cavity formed by the carbon shell, and an iron nitride core within the cavity. Furthermore, the overall particle size of the resulting Yolk-shell carbon-composite iron nitride anode material is approximately 200nm to 260nm, with a carbon shell thickness of 20nm, an average hollow yolk shell size of approximately 50nm to 55nm, and an average particle size of the iron nitride core ranging from 90nm to 125nm. The molar ratio of iron to nitrogen in the iron nitride is 3:1.

[0076] Furthermore, based on the total weight of the obtained Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 70%.

[0077] Example 2

[0078] Preparation of a Yolk-shell carbon composite iron nitride negative electrode material:

[0079] (1) Preparation of a cubic iron oxide precursor: 16.2 g of FeCl₃, 50 mL of deionized water, and 50 mL of a 5.4 M sodium hydroxide solution were mixed to obtain a mixed solution, which was reacted in a water bath at 60°C for 40 min (i.e., the first reaction). The solution was then transferred to a hydrothermal reactor and hydrothermally reacted at 120°C for 4 days (i.e., the second reaction). The mixture was then centrifuged, washed three times with water, three times with ethanol, and dried at 60°C to obtain the cubic iron oxide, referred to as Fe₂O₃ cubes.

[0080] (2) 300 mg of Fe2O3 cubes, 280 mL of deionized water, and 120 mL of ethanol were ultrasonicated for 30 min. Then, 4.6 g of CTAB, 0.7 g of resorcinol, 2 mL of NH4OH, and 1.2 mL of formaldehyde were added in sequence to obtain a mixed slurry, which was stirred for 6 h. The resulting mixed slurry reaction solution was centrifuged, washed with water five times, and dried at 60°C to obtain the first product, which was designated as Fe2O3@RF.

[0081] (3) Take 2.4 g of the first product obtained, heat it to 600 °C at a rate of 3 °C / min under Ar atmosphere and keep it at that temperature for 2 h, then cool it naturally to room temperature to obtain the second product and record it as Fe3O4@C.

[0082] (4) 1.4 g of the second product was added to 500 mL of 3 M hydrochloric acid as an etching solution and stirred for 3 h. The mixture was centrifuged, washed three times with water, and dried at 60°C to obtain the third product, designated Yolk-shell Fe3O4@C.

[0083] (5) Take 30 mg of the third product, heat it to 550°C at a rate of 2°C / min under N2 atmosphere, which is the heating stage, then keep it at 550°C for 5 h under NH3 atmosphere, which is the holding stage, and then naturally cool it to room temperature under N2 atmosphere to obtain a Yolk-shell type carbon composite iron nitride negative electrode material.

[0084] The microstructure of the obtained Yolk-shell carbon composite iron nitride negative electrode material is basically the same as that in Example 1. Moreover, based on the total weight of the obtained Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 68%.

[0085] Example 3

[0086] Preparation of a Yolk-shell carbon composite iron nitride negative electrode material:

[0087] (1) Preparation of a cubic iron oxide precursor: 16.2 g of FeCl₃, 50 mL of deionized water, and 50 mL of a 5.4 M sodium hydroxide solution were mixed to obtain a mixed solution, which was reacted in an 80°C water bath for 20 min (i.e., the first reaction). The solution was then transferred to a hydrothermal reactor and hydrothermally reacted at 100°C for 6 days (i.e., the second reaction). The mixture was then centrifuged, washed three times with water, three times with ethanol, and dried at 60°C to obtain the cubic iron oxide, referred to as Fe₂O₃ cubes.

[0088] (2) 300 mg of Fe2O3 cubes, 280 mL of deionized water, and 120 mL of ethanol were ultrasonicated for 30 min. Then, 4.6 g of CTAB, 0.7 g of resorcinol, 2 mL of NH4OH, and 1.2 mL of formaldehyde were added in sequence to obtain a mixed slurry, which was stirred for 10 h. The resulting mixed slurry reaction solution was centrifuged, washed with water five times, and dried at 60°C to obtain the first product, which was designated as Fe2O3@RF.

[0089] (3) Take 2.4 g of the first product obtained, heat it to 500 °C at a rate of 2 °C / min under Ar atmosphere and keep it at that temperature for 6 h, then cool it naturally to room temperature to obtain the second product and record it as Fe3O4@C.

[0090] (4) 1.4 g of the second product was added to 500 mL of 5 M hydrochloric acid as an etching solution and stirred for 1 h. The mixture was centrifuged, washed three times with water, and dried at 60°C to obtain the third product, designated Yolk-shell Fe3O4@C.

[0091] (5) Take 30 mg of the third product, heat it to 600 °C at a rate of 3 °C / min under N2 atmosphere, which is the heating stage, then keep it at 600 °C for 5 h under NH3 atmosphere, which is the holding stage, and then naturally cool it to room temperature under N2 atmosphere to obtain a Yolk-shell type carbon composite iron nitride negative electrode material.

[0092] The microstructure of the obtained Yolk-shell carbon composite iron nitride negative electrode material is basically the same as that in Example 1. Moreover, based on the total weight of the obtained Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 69%.

[0093] Example 4

[0094] Preparation of a Yolk-shell carbon composite iron nitride negative electrode material:

[0095] The only difference between this embodiment and embodiment 1 is that the temperature reached in the heating stage in step (5) is changed to 650°C, and the temperature in the heat preservation stage is also changed to 650°C.

[0096] The microstructure of the obtained Yolk-shell carbon composite iron nitride negative electrode material is basically the same as that in Example 1. Moreover, based on the total weight of the obtained Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 70%.

[0097] Example 5

[0098] Preparation of a Yolk-shell carbon composite iron nitride negative electrode material:

[0099] The only difference between this embodiment and embodiment 1 is that the temperature of the first reaction in step (1) is changed to 50°C and the time is changed to 60 minutes; the temperature of the second reaction is changed to 70°C and the time is changed to 10 days.

[0100] The overall particle size of the obtained Yolk-shell type carbon composite iron nitride negative electrode material is about 200nm~300nm, of which the thickness of the carbon shell is 18nm, the average size of the yolk shell hollow structure is about 50nm~55nm, the average particle size of the core iron nitride is distributed in 100nm~160nm, and the molar ratio of iron to nitrogen in the iron nitride is 3:1.

[0101] Furthermore, based on the total weight of the obtained Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 80%.

[0102] Example 6

[0103] Preparation of a Yolk-shell carbon composite iron nitride negative electrode material:

[0104] The only difference between this embodiment and embodiment 1 is that the temperature of the first reaction in step (1) is changed to 90°C and the time is changed to 10 minutes; the temperature of the second reaction is changed to 140°C and the time is changed to 2 days.

[0105] The overall particle size of the obtained Yolk-shell type carbon composite iron nitride negative electrode material is about 200nm~400nm, of which the thickness of the carbon shell is 16nm, the average size of the yolk shell hollow structure is about 48nm~55nm, the average particle size of the core iron nitride is distributed in 100nm~180nm, and the molar ratio of iron to nitrogen in the iron nitride is 3:1.

[0106] Furthermore, based on the total weight of the obtained Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 84%.

[0107] Example 7

[0108] Preparation of a Yolk-shell carbon composite iron nitride negative electrode material:

[0109] The only difference between this embodiment and embodiment 1 is that in step (2), the ratio of the Fe2O3 cubes to the total weight of the two polymer monomers is changed to 1:3.5; the volume ratio of the alcohol-water mixed solvent to the NH4OH alkaline pH regulator is changed to 150:1; and the stirring time is changed to 4 hours.

[0110] The overall particle size of the obtained Yolk-shell type carbon composite iron nitride negative electrode material is about 180nm~250nm, of which the thickness of the carbon shell is 18nm, the average size of the yolk shell hollow structure is about 50nm~55nm, the average particle size of the inner core iron nitride is distributed in the range of 90nm~125nm, and the molar ratio of iron to nitrogen in the iron nitride is 3:1.

[0111] Furthermore, based on the total weight of the obtained Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 80%.

[0112] Example 8

[0113] Preparation of a Yolk-shell carbon composite iron nitride negative electrode material:

[0114] The only difference between this embodiment and embodiment 1 is that in step (2), the ratio of the Fe2O3 cubes to the total weight of the two polymer monomers is changed to 1:7.5; the volume ratio of the alcohol-water mixed solvent to the NH4OH alkaline pH regulator is changed to 300:1; and the stirring time is changed to 12 hours.

[0115] The overall particle size of the obtained Yolk-shell type carbon composite iron nitride negative electrode material is about 220nm~300nm, of which the thickness of the carbon shell is 26nm, the average size of the yolk shell hollow structure is about 50nm~55nm, the average particle size of the inner core iron nitride is distributed in the range of 90nm~125nm, and the molar ratio of iron to nitrogen in the iron nitride is 3:1.

[0116] Furthermore, based on the total weight of the obtained Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 60%.

[0117] Example 9

[0118] Preparation of a Yolk-shell carbon composite iron nitride negative electrode material:

[0119] This example differs from Example 1 only in that CTAB is not added in step (2).

[0120] The overall particle size of the obtained Yolk-shell type carbon composite iron nitride negative electrode material is about 200nm~260nm, of which the thickness of the carbon shell is 17nm, the average size of the yolk shell hollow structure is about 50nm~55nm, the average particle size of the core iron nitride is distributed in the range of 90nm~125nm, and the molar ratio of iron to nitrogen in the iron nitride is 3:1.

[0121] Furthermore, based on the total weight of the obtained Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 70%.

[0122] Example 10

[0123] Preparation of a Yolk-shell carbon composite iron nitride negative electrode material:

[0124] The only difference between this embodiment and embodiment 1 is that the heating rate of the calcination treatment in step (3) is changed to 1°C / min, the holding temperature is changed to 400°C, and the holding time is changed to 8h.

[0125] The overall particle size of the obtained Yolk-shell type carbon composite iron nitride negative electrode material is about 200nm~260nm, the thickness of the carbon shell is 20nm, the average size of the yolk shell hollow structure is about 50nm~55nm, the average particle size of the inner core iron nitride is distributed in the range of 90nm~125nm, and the molar ratio of iron to nitrogen in the iron nitride is 3:1.

[0126] Furthermore, based on the total weight of the obtained Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 70%.

[0127] Example 11

[0128] Preparation of a Yolk-shell carbon composite iron nitride negative electrode material:

[0129] The only difference between this embodiment and embodiment 1 is that the molar concentration of the etching solution of the HCl aqueous solution used in step (4) is changed to 1 M, and the etching time is changed to 4 h.

[0130] The overall particle size of the obtained Yolk-shell type carbon composite iron nitride negative electrode material is about 200nm~260nm, of which the thickness of the carbon shell is 20nm, the average size of the yolk shell hollow structure is about 40nm~45nm, the average particle size of the core iron nitride is distributed in 100nm~150nm, and the molar ratio of iron to nitrogen in the iron nitride is 3:1.

[0131] Furthermore, based on the total weight of the obtained Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 80%.

[0132] Example 12

[0133] Preparation of a Yolk-shell carbon composite iron nitride negative electrode material:

[0134] The only difference between this embodiment and embodiment 1 is that the molar concentration of the etching solution of the HCl aqueous solution used in step (4) is changed to 7 M, and the etching time is changed to 0.5 h.

[0135] The overall particle size of the obtained Yolk-shell type carbon composite iron nitride negative electrode material is about 180nm~270nm, the thickness of the carbon shell is 20nm, the average size of the yolk shell hollow structure is about 50nm~55nm, the average particle size of the core iron nitride is distributed in the range of 60nm~130nm, and the molar ratio of iron to nitrogen in the iron nitride is 3:1.

[0136] Furthermore, based on the total weight of the obtained Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 65%.

[0137] Example 13

[0138] Preparation of a Yolk-shell carbon composite iron nitride negative electrode material:

[0139] The only difference between this embodiment and embodiment 1 is that the heating stage, the heat preservation stage and the cooling stage in step (5) are all changed to be carried out under an ammonia atmosphere, and the heating temperature and the heat preservation temperature are both changed to 480°C.

[0140] The overall particle size of the obtained Yolk-shell type carbon composite iron nitride negative electrode material is about 200nm~260nm, the thickness of the carbon shell is 20nm, the average size of the yolk shell hollow structure is about 50nm~55nm, the average particle size of the inner core iron nitride is distributed in the range of 90nm~125nm, and the molar ratio of iron to nitrogen in the iron nitride is 3:1.

[0141] Furthermore, based on the total weight of the obtained Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 70%.

[0142] Comparative Example 1

[0143] Preparation of a composite negative electrode material:

[0144] The only difference between this comparative example and Example 1 is that step (4) is not performed, that is, no etching treatment is performed.

[0145] The SEM image of the obtained composite negative electrode material is shown in Figure 11 .Depend on Figure 11 It can be seen that although a carbon layer coating is formed, the overall morphology of the composite material does not change much, and no Yolk-shell microstructure is formed.

[0146] Comparative Example 2

[0147] Preparation of a composite negative electrode material:

[0148] The only difference between this comparative example and Example 1 is that step (2) is not performed, and the cubic iron oxide precursor obtained in step (1) is directly subjected to subsequent calcination, etching and nitriding treatment.

[0149] Test Method

[0150] Sodium ion battery sample assembly and cycle stability testing

[0151] The negative electrode active materials obtained from each example and comparative example, the conductive material (acetylene black), and the polyvinylidene fluoride binder (PVDF) were mixed in a weight ratio of (7:2:1), and then N-methylpyrrolidone (NMP) was added to adjust the viscosity. The mixture was then dispersed evenly using a high-speed disperser and coated on copper foil. The mixture was then vacuum-dried at 60°C overnight. The resulting working electrode active material loading was 0.8 mg / cm 2 ~1.0mg / cm 2 A sodium sheet was used as the counter electrode, the electrolyte system was 1M NaClO4 / EC:DMC (1:1), and a microporous polypropylene membrane (Celgard 2400) was used as the separator.

[0152] Cyclic stability test: at 1Ag -1 At a current density of , the battery samples obtained in each embodiment and comparative example were cycled for 2000 cycles, and then their discharge specific capacities were tested.

[0153] The obtained performance test results are shown in Table 1. The I of the composite negative electrode materials obtained in each embodiment and comparative example is D / I G The values ​​are the same as those in Table 1.

[0154] Table 1

[0155]

[0156] From the above description, it can be seen that compared with Comparative Examples 1 and 2, the above-mentioned embodiments of the present invention achieve the preparation of Yolk-shell carbon composite iron nitride negative electrode materials with excellent and stable structures. Compared with solid structures with similar components, the special Yolk-shell structure can provide excellent conductivity for the resulting sodium ion battery, while the cavity and the outer carbon shell can effectively suppress the stress caused by the volume change of the core active particles, improve the reaction stability and conductivity, and ultimately make the resulting sodium ion battery exhibit higher cycling stability.

[0157] Specifically, by comparing Examples 5 and 6 with Example 1, it can be seen that by optimizing the conditions of the first reaction and the second reaction, nano-iron oxide cubes with more uniform size and clearer morphology can be obtained, thereby more effectively improving the stability of the final iron nitride core.

[0158] Comparing Examples 7 and 8 with Example 1, it can be seen that in step (2), by optimizing the weight ratio of the cubic iron oxide precursor to the polymer monomer, the volume ratio of the solvent to the alkaline pH regulator, and the preferred stirring time, the deposition polymerization rate of the polymer monomer can be more effectively controlled, and the morphology of the formed polymer layer can be optimized, thereby promoting the formation of a more stable carbon layer after subsequent calcination.

[0159] Comparing Example 9 with Example 1, it can be seen that when the polymer monomer includes resorcinol and formaldehyde, the surfactant CTAB is preferably added to the mixed slurry, and the weight ratio of the surfactant CTAB to the cubic iron oxide precursor is (15-16):1, which can make the RF layer more uniformly distributed and the thickness more moderate, while also suppressing the reduction of internal active sites caused by excessive coating, thereby more significantly optimizing the sodium storage capacity and electrochemical cycle performance of the obtained composite negative electrode material.

[0160] Comparing Example 10 with Example 1, it can be seen that the preferred calcination conditions in step (3) can reduce cracking or structural inhomogeneity caused by excessive temperature gradients, and more effectively promote the formation of carbon, prompting the iron in the inner core iron oxide to be converted to a lower valence state, which is conducive to the subsequent conversion into a structurally stable nitride. At the same time, it more effectively balances the integrity of the obtained carbon layer and the suppression of side reactions, ultimately obtaining a more stable composite negative electrode material.

[0161] Comparing Examples 11 and 12 with Example 1, it can be seen that the etching treatment conditions in the preferred step (4) can more efficiently remove iron oxide with a more appropriate thickness ratio, create a more stable internal loose space, and thus more significantly improve the cycle stability and rate performance of the material.

[0162] Comparing Example 13 with Example 1, it can be seen that the conditions for the nitriding treatment in the preferred step (5) can make the crystals of the inner core iron nitride more ordered, while also more effectively maintaining the structure of the outer carbon shell, thereby making the structure of the obtained composite negative electrode material more complete and stable, and the electrochemical performance, especially the cyclability, more outstanding.

[0163] It should be noted that the terms "first," "second," and the like in the specification and claims of this application are used to distinguish similar objects, and are not necessarily used to describe a specific order or precedence. It should be understood that the terms used in this manner are interchangeable where appropriate, so that the embodiments of the application described herein can, for example, be implemented in an order other than that described herein.

[0164] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A Yolk-shell carbon composite iron nitride negative electrode material, comprising a shell, a cavity formed by the shell, and a core disposed in the cavity, characterized in that: The particle size of the Yolk-shell carbon composite iron nitride negative electrode material is 180nm to 400nm; The outer shell is a carbon shell, and the thickness of the carbon shell is 10nm to 30nm; The inner core is cubic iron nitride, and the particle size of the cubic iron nitride is 60nm to 180nm.

2. The Yolk-shell carbon composite iron nitride negative electrode material according to claim 1, characterized in that: In the cubic iron nitride, the molar ratio of the iron element to the nitrogen element is (2-4):

1.

3. The Yolk-shell carbon composite iron nitride negative electrode material according to claim 1 or 2, characterized in that: Based on the total weight of the Yolk-shell carbon composite iron nitride negative electrode material being 100%, the weight proportion of the cubic iron nitride is 60% to 85%, preferably 60% to 80%.

4. The Yolk-shell carbon composite iron nitride negative electrode material according to any one of claims 1 to 3, characterized in that The particle size of the Yolk-shell carbon composite iron nitride negative electrode material is 200nm to 260nm; The thickness of the carbon shell is 20±2 nm; The particle size of the cubic iron nitride is 90nm to 125nm; Preferably, the Raman spectrum of the Yolk-shell carbon composite iron nitride negative electrode material includes a D peak and a G peak, and the intensity ratio ID / IG of the D peak to the G peak is 0.85 to 0.

95.

5. A method for preparing a Yolk-shell carbon composite iron nitride negative electrode material according to any one of claims 1 to 4, characterized in that: include: Step S1, preparing a cubic iron oxide precursor; Step S2, adding the cubic iron oxide precursor, polymer monomers, and an alkaline pH regulator into a solvent to prepare a mixed slurry; stirring the mixed slurry to polymerize the polymer monomers on the surface of the cubic iron oxide precursor to form a polymer layer, thereby obtaining a first product; Step S3, the first product is calcined to convert the polymer layer into the carbon shell, thereby obtaining a second product; Step S4, etching the cubic iron oxide precursor in the second product to reduce the cubic volume of the cubic iron oxide precursor and form the cavity to obtain a third product; Step S5: performing a nitriding treatment on the third product to transform the shrunken cubic iron oxide precursor into the cubic iron nitride, thereby obtaining the Yolk-shell carbon composite iron nitride negative electrode material.

6. The method for preparing a Yolk-shell carbon composite iron nitride negative electrode material according to claim 5, characterized in that: The step S1 further includes: Step S1-1, adding an iron source and an oxygen source to water to obtain a mixed solution; Step S1-2, the mixed solution undergoes a first reaction and a second reaction in sequence to obtain the cubic iron oxide precursor; The molar ratio of the iron element in the iron source to the oxygen element in the oxygen source is 1:(2.7-3.0); and / or, The reaction temperature of the first reaction is 60° C. to 80° C., and the reaction time is 20 min to 40 min; and / or, The reaction temperature of the second reaction is 80° C. to 120° C., the reaction time is 4 to 6 days, and the second reaction is carried out in a reactor; Preferably, the iron source is selected from one or more of ferric chloride, ferric sulfate and ferric nitrate; and / or, the oxygen source is selected from one or more of hydroxides; More preferably, the hydroxide is added in the form of an aqueous solution with a molar concentration of 5M to 6M, and the hydroxide is sodium hydroxide and / or potassium hydroxide.

7. The method for preparing the Yolk-shell carbon composite iron nitride negative electrode material according to claim 5 or 6, characterized in that: In the step S2, The weight ratio of the cubic iron oxide precursor to the polymer monomer is 1: (3.5-7.5), preferably 1: (4.4-4.5); and / or, The volume ratio of the solvent to the alkaline pH regulator is (200±20):1; and / or, The stirring time is 6h to 10h; and / or, Preferably, the alkaline pH regulator is NH4OH; More preferably, the polymer monomer includes resorcinol and formaldehyde, and the polymer layer is a resorcinol-formaldehyde layer; or, the polymer monomer is dopamine, and the polymer layer is a polydopamine layer.

8. The method for preparing a Yolk-shell carbon composite iron nitride negative electrode material according to any one of claims 5 to 7, characterized in that: In step S3, the heating rate of the calcination treatment is 2°C / min to 3°C / min, the holding temperature is 500°C to 600°C, and the holding time is 2h to 6h; Preferably, the calcination treatment is performed under a protective atmosphere, and the protective atmosphere is nitrogen and / or argon.

9. The method for preparing a Yolk-shell carbon composite iron nitride negative electrode material according to any one of claims 5 to 8, characterized in that: In step S4, the etching treatment includes: immersing the second product in an acidic etching solution with a concentration of 3M to 5M, and stirring for 1 hour to 3 hours to obtain the third product; Preferably, the acidic etching solution is selected from one or more of a hydrochloric acid aqueous solution, a nitric acid aqueous solution, a phosphoric acid aqueous solution and a hydrofluoric acid aqueous solution.

10. The method for preparing a Yolk-shell carbon composite iron nitride negative electrode material according to any one of claims 5 to 9, characterized in that: In step S5, the nitriding treatment includes the following steps: a heating stage in a protective atmosphere, a heat preservation stage in a nitrogen source atmosphere, and a cooling stage in a protective atmosphere; Preferably, the heating rate in the heating stage is 2°C / min to 3°C / min until the temperature reaches 500°C to 700°C; the holding temperature in the holding stage is 550°C to 700°C, and the holding time is 3h to 5h; More preferably, the nitrogen source atmosphere is an ammonia atmosphere; and / or the protective atmosphere is nitrogen and / or argon; Further preferably, the ammonia atmosphere is achieved by: introducing ammonia gas into the nitriding system; and / or, adding ammonia water into the nitriding system.

11. A negative electrode plate, characterized in that: The negative electrode plate includes the Yolk-shell type carbon composite iron nitride negative electrode material according to any one of claims 1 to 4; or, the negative electrode plate includes the Yolk-shell type carbon composite iron nitride negative electrode material prepared by the preparation method of the Yolk-shell type carbon composite iron nitride negative electrode material according to any one of claims 5 to 10.

12. A sodium ion battery comprising a negative electrode plate, characterized in that: The negative electrode plate is the negative electrode plate according to claim 11.